Relationship Between Family Support And Successful Aging In The Elderly - Engkus Kuswara; Aneng Yuningsih; Sri Wianti (Jurnal Vocational Nursing Sciences (VNUS), 2020)
Success in extending life expectancy should be viewed wisely as a manifestation of the success of human resource development in the present. However, it cannot be denied that with the increasing number of elderly people, this has the potential to cause various problems. One of them is related to the reduced level of population productivity. The elderly group often becomes unproductive because of the decline in their physical and mental conditions. This study aims to analyze the relationship between family support and successful aging in the elderly in Panulisan Dayeuhluhur Village. The research design used is correlational or relationship research with a cross sectional approach. The number of samples in this study were 52 of the 1073 elderly population in Panulisan Barat Village with a randomized proportional sampling technique. From the results of the Colmogorov-Smirnov test, it is known that there is a significant relationship between family support and successful aging in the elderly, with a p value of 0.000 which is smaller than an alpha of 0.05. Suggestions for nursing practitioners from the results of this study can be used as input to bring active efforts to health workers, especially gerontic nurses in the community in giving a social impression to the elderly, so that it is expected to produce better living conditions for the elderly. Further research is expected to dig deeper into the dimensions of family support in an effort to improve Successful Aging in the elderly with a deeper analysis of each dimension